2018
DOI: 10.1002/ejic.201800330
|View full text |Cite
|
Sign up to set email alerts
|

A Deca‐9‐Fluorenolato‐deca‐Samarium Oxide Cage

Abstract: The 9-fluorenone (fn) ketyl in [Yb III (DippForm) 2 -(fn · -O)] {DippForm = N,N′-bis(2,6-diisopropylphenyl)formamid-inate}, underwent reduction to the dianion ({C 13 H 8 }-O) upon single electron transfer from Sm II I 2 (thf ) 2 . The dianion was ob- [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…During our studies in exploring N-donor alternatives to the cyclopentadienyl family of ligands, we examined the reactivity of divalent rare-earth (Yb 2+ , Sm 2+ ) complexes coordinated by the sterically demanding N , N ′-bis­(2,6-diisopropylphenyl)­formamidinate (DippForm) ligand, namely, [Yb­(DippForm) 2 (thf) n ] ( n = 2 ( 1aYb ), n = 1 ( 1bYb ), and [Sm­(DippForm) 2 (thf) 2 ] ( 1aSm ). − , The reactivity of these complexes included the concomitant redox chemistry upon treatment with CX (X = O or S) containing molecules, ,, one of which was CS 2 . In the reaction between CS 2 and 1aSm , the resulting product of redox chemistry is a C–S coupled species [Sm 2 (DippForm) 4 (μ-1η 2 ( C , S ):2κ­( S″ , S‴ )-SC–S–C-S 2 )] ( 2 , Scheme ).…”
mentioning
confidence: 99%
“…During our studies in exploring N-donor alternatives to the cyclopentadienyl family of ligands, we examined the reactivity of divalent rare-earth (Yb 2+ , Sm 2+ ) complexes coordinated by the sterically demanding N , N ′-bis­(2,6-diisopropylphenyl)­formamidinate (DippForm) ligand, namely, [Yb­(DippForm) 2 (thf) n ] ( n = 2 ( 1aYb ), n = 1 ( 1bYb ), and [Sm­(DippForm) 2 (thf) 2 ] ( 1aSm ). − , The reactivity of these complexes included the concomitant redox chemistry upon treatment with CX (X = O or S) containing molecules, ,, one of which was CS 2 . In the reaction between CS 2 and 1aSm , the resulting product of redox chemistry is a C–S coupled species [Sm 2 (DippForm) 4 (μ-1η 2 ( C , S ):2κ­( S″ , S‴ )-SC–S–C-S 2 )] ( 2 , Scheme ).…”
mentioning
confidence: 99%
“…Interestingly, most of them comprising two N­(dipp) donor groups per ligand are joined by a shorter bridge between the two nitrogen atoms and contain two coordinated thf molecules per Ln cation. These are Yb­(II) formamidinates (NN = HC­(Ndipp) 2 – , four-membered metallacycle) and Eu­(II) bis­(imino)­acenaphthenate (NN = C 12 H 6 (Ndipp) 2 – , five-membered metallacycle) . Closely related iminopyridinates of Sm­(II), Eu­(II), and Yb­(II) (NN = C 5 H 3 N­(2-Ndipp)­(6-dipp) − , four-membered metallacycle) also possess the same structures. , Only the coordination of even more sterically demanding guanidinates lead to complexes with one thf molecule per Yb 2+ cation (NN = R 2 NC­(Ndipp) 2 – , R = i Pr, cyclohexyl, four-membered metallacycle). , Apparently, the longer bridge in Nacnac complexes (six-membered metallacycle) results in wider N–Ln–N bite angles and in farther separated dipp substituents, thus covering a larger part of the coordination sphere.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, most of them comprising two N(dipp) donor groups per ligand are joined by a shorter bridge between the two nitrogen atoms and contain two coordinated thf molecules per Ln cation. These are Yb(II) formamidinates (NN = HC(Ndipp) 2 − , four-membered metallacycle) 53 and Eu(II) bis(imino)acenaphthenate (NN = C 12 H 6 (Ndipp) 2 − , five-membered metallacycle). 54 Closely related iminopyridinates of Sm(II), Eu(II), and Yb(II) (NN = C 5 H 3 N(2-Ndipp)(6-dipp) − , four-membered metallacycle) also possess the same structures.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Related to this, the CÀ O bond length (1.539(5) Å) is very long, and significantly longer than other crystallographically characterised reduced ketone units in complexes of electropositive metals. [9][10][11][12] For example, alkali metal complexes of dianionic aromatic ketones show CÀ O bond length of ca. 1.38-1.41 Å.…”
Section: Resultsmentioning
confidence: 99%
“…DFT calculations on the model complex [Na 2 (OCPh 2 )] afforded an NPA charge of + 0.38 on the central carbon atom and thus it had been concluded that these species cannot be regarded as vicinal dianions. In addition, some lanthanoid complexes [11] and transition metal complexes of groups 4-6 [12] form complexes with significantly reduced ketone fragments, largely for aromatic ketones. The Ln examples show dianionic ketone fragments with planar carbonyl centres similar to those for alkali metal complexes, and the transition metal examples show significantly more pyramidalization at the carbonyl unit in a metallaoxirane ring with more covalency and interaction of a metal d-orbital with the R 2 CO π*-orbital.…”
Section: Introductionmentioning
confidence: 99%